Kayexalate-Induced Esophageal Ulceration in a Patient with Decompensated Cirrhosis: A Review of the Literature - Kishore Kumar; Harish Patel; Muhammad Saad; Ahmed Baiomi; Anil Dev (Case Reports in Gastrointestinal Medicine)
Hyperkalemia is one of the most common electrolyte abnormalities encountered in clinical practice. The treatment of hyperkalemia includes removal of excess potassium from the body using cation exchange resins, e.g., sodium polystyrene sulfonate (Kayexalate) is one of the most practiced modalities in clinical medicine. Colonic mucosal necrosis and perforation are the serious gastrointestinal side effects associated with sodium polystyrene sulfonate (SPS) use, which have been reported with or without concomitant use of sorbitol. However, the catastrophic bleeding esophageal ulcer has been rarely described in our literature search. Due to the risk of colonic necrosis, the FDA has issued a warning to avoid concomitant sorbitol use with Kayexalate. We present an individual with acute hematemesis due to bleeding esophageal ulcer immediately after treatment with Kayexalate therapy. Though the exact mechanism by which Kayexalate causes esophageal ulcer to be elucidated, nonetheless it is worthwhile to be vigilant about its potential adverse effects. Our case highlights the rare but certainly the life-threatening complication of Kayexalate therapy.